The Outcomes of Decorated Prolines in the Discovery of Antimicrobial Peptides from Temporin‐L. (3rd June 2019) - Buommino, Elisabetta; Carotenuto, Alfonso; Antignano, Ignazio; Bellavita, Rosa; Casciaro, Bruno; Loffredo, Maria Rosa; Merlino, Francesco; Novellino, Ettore; Mangoni, Maria Luisa; Nocera, Francesca Paola; Brancaccio, Diego; Punzi, Pasqualina; et al.
Abstract: Previously, we identified a potent antimicrobial analogue of temporin L (TL), [Pro 3 ]TL, in which glutamine at position 3 was substituted with proline. In this study, a series of analogues in which position 3 is substituted with non‐natural proline derivatives, was investigated for correlations between the conformational properties of the compounds and their antibacterial, cytotoxic, and hemolytic activities. Non‐natural proline analogues with substituents at position 4 of the pyrrolidine ring were considered. Structure–activity relationship (SAR) studies of these analogues were performed by means of antimicrobial and cytotoxicity assays along with circular dichroism (CD) and NMR spectroscopic analyses for selected compounds. The most promising peptides were additionally evaluated for their activity against some representative veterinary microbial strains to compare with those from human strains. We identified novel analogues with interesting properties that make them attractive lead compounds. Abstract : Amped up AMPs ! By using some non‐canonical proline derivatives of the antimicrobial peptide (AMP) temporin L, we investigated the correlation between the conformational properties of the synthesized compounds and their antibacterial, cytotoxic, and hemolytic activities. A SAR study was performed with CD and NMR spectroscopic analyses. We identified novel analogues with interesting properties that make them promising leads for further chemical optimization.